Effects of IPSAS Adoption in Public Institutions in Romania on the Quality of Financial Reporting - Elena Alina OLARU (COLBEA) (CECCAR Business Review, 2023)

(untitled)
This paper examines the practical improvement on the quality of financial reporting in the Romanian public institutions after implementing IPSAS. To test our hypothesis, we used a questionnaire addressed to the accounting professionals from the local public administration, in which 164 respondents participated. In this revision, we use a linear regression analysis method to examine the relationship between the implementation of IPSAS and the quality of financial reporting in the Romanian public institutions. The introduction of IPSAS, as demonstrated by empirical studies, is significantly positively related to the quality of financial reporting in the Romanian public institutions. The findings of this research recommend that regulators take appropriate measures to ensure compliance by those responsible for the preparation of financial statements of public sector entities. Efforts should also be made to improve the quality of disclosure of relevant financial reports to help users make beneficial economic decisions.